THE INFLUENCE OF STACKING YARD UTILIZATION AND OPERATIONAL PERFORMANCE ON LOADING AND UNLOADING PRODUCTIVITY AT THE KOJA CONTAINER TERMINAL JOINT OPERATION - Suryadi, Slamet; Wisnawati, Devi; Maulani, Nissa Fitri; Baiquni, Maulana Akbar; Zulkarnaen, Dedy (Meteor STIP Marunda, 2024)
Indonesia is the largest archipelagic country in the world. Indonesia has extraordinary natural resources and human resources because of its strategic location between the continents of Asia and Australia and between the Indian and Pacific Oceans. Ports as trade gateways and providers of public services play a very important role in economic movements, and the economy plays an important role. very important in the economy. In the accumulation field utilization variable (X1) there are 13 indicators which are statements to be answered based on the suitability felt by the respondent. The questionnaire was created using a Likert scale which has answer options ranging from Strongly, no, disagree, disagree, not sure. , Agree and completely agree "Maximum loading and unloading productivity quality and in accordance with the set targets"; "The level of use of stacking yards for export activities is quite high" with an average of 4.5455, which means that respondents strongly agree. On the other hand, the lowest average is Information regarding the relationship between operational performance and loading and unloading productivity can be used to direct policy and strategic decisions.